2007
DOI: 10.1002/mrc.2022
|View full text |Cite
|
Sign up to set email alerts
|

Structure elucidation of thermal degradation products of amlodipine

Abstract: Thermal degradation of amlodipine base causes intramolecular reactions affording three cyclic products, referred to as AMLDEG-I, AMLDEG-II, and AMLDEG-III, respectively. AMLDEG-I is a cyclized product formed by intramolecular elimination of ammonia from amlodipine. AMLDEG-II is a positional isomer of AMLDEG-I. AMLDEG-III is also intramolecular cyclisation product. The three degradation products were isolated by column chromatography and characterized by FT-IR and 1H and 13C NMR spectroscopy data. The AMLDEG-II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…A few articles are available on photostability studies of AM, where the thermal degradation kinetics are reported from 0 h to 108 h [17] , [18] , [19] , [20] . There exists report on isolation and characterization of three thermal degradation products of AM, which were formed due to intramolecular reactions and cyclization [21] . Moreover, there are few reports on isolation and characterization of process-related impurities of AM and accelerated stability studies.…”
Section: Introductionmentioning
confidence: 99%
“…A few articles are available on photostability studies of AM, where the thermal degradation kinetics are reported from 0 h to 108 h [17] , [18] , [19] , [20] . There exists report on isolation and characterization of three thermal degradation products of AM, which were formed due to intramolecular reactions and cyclization [21] . Moreover, there are few reports on isolation and characterization of process-related impurities of AM and accelerated stability studies.…”
Section: Introductionmentioning
confidence: 99%
“…The compound formed by the aromatization of the ring (pyridine derivative) is the only photoproducts known and described in the literature so far [16] , [17] , [18] . A few studies were performed for thermal degradation of amlodipine showing the formation of 3 [19] or 5 main transformation products [20] .…”
Section: Introductionmentioning
confidence: 99%
“…1,4-Dihydropyridine substance frameworks forming an important class of Ca +2 channel blockers such as Nifedipin and Amlodipine are clinically significant antihypertensive drugs [1][2][3][4]. First synthesis of 1,4-dihydropyridine from an aldehyde, b-keto ester and an amine was described by Hä ntzsch in 1882 [5].…”
Section: Introductionmentioning
confidence: 99%